Assessing the Impact of Temperature and Rainfall on Forest Cover and Vegetation Dynamics in Chakaria, Cox's Bazar - Rahman, Muhammad Khalilur; Khan, Ebadullah (The Jahangirnagar Review, 2025)
This research investigates the relationship between climatic factors, forest cover, and vegetation dynamics in Chakaria, Cox's Bazar, Bangladesh, concentrating on the years 2015, 2020, and 2024. By employing GIS and remote sensing methodologies, such as Landsat 8 OLI satellite imagery, NDVI analysis, and supervised classification, the study examines seasonal fluctuations in forest cover and vegetation during pre-monsoon and post-monsoon periods. Temperature and rainfall data, collected from the Bangladesh Agricultural Research Council and the Center for Hydrometeorology and Remote Sensing (CHRS) Data Portal, offer valuable insights into seasonal climatic patterns.The findings reveal distinct seasonal patterns, with temperature exerting a more pronounced impact on vegetation degradation during the pre-monsoon season, whereas rainfall significantly supports vegetation recovery in the post-monsoon period. Regression analyses indicate a moderate to strong correlation between climatic variables and forest cover dynamics, with temperature and rainfall influencing forest health and NDVI values differently. The supervised classification of land-use and land-cover changes achieved high accuracy, validated through Kappa tests, underscoring the reliability of the methodological approach.This study highlights the critical role of climatic variables in shaping forest ecosystems and vegetation health, particularly in climate-vulnerable regions like Chakaria. The research underscores the need for sustainable forest management practices and evidence-based policies to mitigate climate-induced challenges and ensure ecological resilience. The integration of climate data with spatial analyses provides valuable insights into the impacts of climate variability, offering a robust framework for future studies aiming to predict and manage the effects of environmental change in deltaic regions.